(untitled) (Journal of Engineering, 2012)
Stripping is one of the major distresses within asphalt concrete pavements caused due to penetration of water within the interface of asphalt-aggregate matrix. In this work, one grade of asphalt cement (40-50) was mixed with variable percentages of three types of additives (fly ash, fumed silica, and phosphogypsum) to obtained an modified asphalt cement to resist the effect of stripping phenomena .The specimens have been tested for physical properties according to AASHTO. The surface free energy has been measured by using two methods namely, the wilhelmy technique and the Sessile drop method according to NCHRP-104 procedures. Samples of asphalt concrete using different asphalt cement and modified asphalt cement percentages(4.1,4.6 and 5.6) were prepared and tested for stripping phenomena by using Marshall Immersion method (The index of retained stability test(I.R.S) ≥75 %. When using Sessile drop method the value of surface free energy of asphalt cement grade (40-50) was about 8.8 ergs/cm2 , while when using Wilhelmy technique the value of surface free energy of asphalt cement was 30.71 ergs/cm2. Finally, a mathematical relationship was obtained by using (SPSS) Software between the strippingasphalt concrete using conditioned and unconditioned specimens data (I.R.S) %, the contact angle, the total surface free energy for asphalt cement and modified asphalt cement with fume silica.